2011
DOI: 10.3109/09637486.2011.602052
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ready-to-eat cereal consumption on energy intake, body weight and anthropometric measurements: results from a randomized, controlled intervention trial

Abstract: The objective of this work was to determine the effect of consumption of ready-to-eat cereal (RTEC) in the evening in place of a normal evening snack on body weight, anthropometric measurements and energy intake in overweight individuals. Seventy overweight participants who were self-reported habitual evening snackers were assigned to either the control or treatment group. For 6 weeks the treatment group consumed RTEC instead of their normal evening snack. Body weight, anthropometric and food intake measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In contrast, most of the intervention studies that added cereal at breakfast did not show any significant impact on measures of weight ( 85 , 86 , 90 , 91 , 101 , 102 , 106 ). It is often difficult to distinguish the effect of a breakfast meal from the effect of breakfast cereals specifically; there is thus a need for larger long-term intervention trials comparing the impact of different types of breakfast cereals when consumed at breakfast.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…In contrast, most of the intervention studies that added cereal at breakfast did not show any significant impact on measures of weight ( 85 , 86 , 90 , 91 , 101 , 102 , 106 ). It is often difficult to distinguish the effect of a breakfast meal from the effect of breakfast cereals specifically; there is thus a need for larger long-term intervention trials comparing the impact of different types of breakfast cereals when consumed at breakfast.…”
Section: Resultsmentioning
confidence: 76%
“…However, that study did not provide information on the control cereal used for comparison and required 2 servings/d to be consumed ( 103 ). The other three 6-wk studies had differing results: 1 reported a beneficial effect with an oat-based breakfast cereal taken at 2 meals in a day ( 104 ); another also found that increased breakfast cereal consumption assisted weight loss in a hypocaloric diet ( 105 ); and another found no effect when evening snacks were replaced by RTEC ( 106 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consuming RTEC in amounts ranging from 33–60 g/d did not consistently improve dietary intake or anthropometric measures [ 51 – 53 ], and these studies did not report whether and what types of foods RTEC supplemented, except in the study by Kirk et al [ 51 ] who supplemented bread and toast. The study by Kirk et al [ 51 ] also reported a greater decrease in the percent contribution of biscuits and cakes to mean daily energy intake compared with the control group who received no advice to consume RTEC for 12 weeks (-6.0 %E vs -1.4 %E); one or two servings of RTEC for 12 weeks did not affect body weight in children [ 53 ]; but when RTEC and milk was consumed in place of the usual evening snack (food type not reported), an increase in evening energy intake (+500 kJ) was found [ 52 ].…”
Section: Reviewmentioning
confidence: 99%
“…There were 14 observational studies [ 4 , 5 , 9 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ] and 14 RCTs [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ] evaluating the relationship of RTEC with body weight outcomes. Most observational studies were cross-sectional in design, with only 3 prospective analyses from cohorts or longitudinal RCTs [ 9 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%